Assessment of serum galectin-3, methylated arginine and Hs-CRP levels in type 2 diabetes and prediabetes - Atalar, Mehmet Nuri; Abuşoğlu, Sedat; Ünlü, Ali; Tok, Oğuzhan; İpekçi, Süleyman Hilmi; Baldane, Süleyman; Kebapcılar, Levent (Life sciences (1973), 2019)
Galectin-3 is associated with the process of inflammation and fibrosis. The aim of this study was both to evaluate of galectin-3, methylated arginines and hs-CRP in subjects with type 2 diabetes and prediabetes and to investigate a relation between serum galectin-3, methylated arginines and hs-CRP levels. In this study, all subjects were defined as the control group, type 2 diabetes (n = 84) by fasting plasma glucose and prediabetes (n = 34) by 75-g oral glucose tolerance test. Also, participants with type 2 diabetes were divided into as group I (HbA1c ≤7%, n = 40) and group II (HbA1c ≥7%, n = 44). The analysis of serum methylated arginines levels was analyzed by tandem mass spectrometry. Galectin-3 levels were determined via chemiluminescent microparticle immunoassay (CMIA). Serum galectin-3, ADMA, L-NMMA and SDMA levels were significantly lower in the control group (13.3 ± 3.42; 0.630 (0.13–1.36); 0.176 (0.02–0.53); 0.115 (0.04–0.26), respectively) compared to diabetic subjects (15.71 ± 4.22; 0.825 (0.23–2.80); 0.366 (0.08–1.41); 0.1645 (0.06–0.47), p = 0.002, p = 0.01, p = 0.001 and p = 0.006, respectively). Galectin-3 was positively correlated with hs-CRP (r = 0.295 p = 0.001), L-NMMA (r = 0.181 p = 0.022), HbA1c (r = 0.247 p = 0.002), neopterin (r = 0.160 p = 0.045) and FPG (r = 0.207 p = 0.001) respectively. Also, there was positively correlated ADMA with FPG (r = 0.192 p = 0.016) and eAG (r = 0.235 p = 0.003). Thus, galectin-3 might be a useful prognostic marker in the population with prediabetes and diabetes. Moreover, it can be a marker showing the condition of developing complications in diabetic patients. •Galectin-3, methylated arginines and hs-CRP in subjects with type 2 diabetes and prediabetes•The levels of these biomarkers were found higher in participants with type 2 diabetes.•The levels of these molecules may be used to identify the subjects predisposed to diabetes.